2009
DOI: 10.1007/s11999-009-0920-9
|View full text |Cite
|
Sign up to set email alerts
|

Are Away Rotations Critical for a Successful Match in Orthopaedic Surgery?

Abstract: Surveys have suggested one of the most important determinants of orthopaedic resident selection is completion of an orthopaedic clerkship at the program director's institution. The purpose of this study was to further elucidate the significance of visiting externships on the resident selection process. We retrospectively reviewed data for all medical students applying for orthopaedic surgery residency from six medical schools between 2006 and 2008, for a total of 143 applicants. Univariate and multivariate reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 10 publications
2
77
0
Order By: Relevance
“…42 In a study from six orthopedic surgery residencies, a regression analysis demonstrated that the number of away rotations was associated with matching to orthopedic surgery. 43 However, plastic surgery and orthopedic surgery are highly competitive disciplines and may not reflect all residency matches.…”
Section: Electivesmentioning
confidence: 99%
“…42 In a study from six orthopedic surgery residencies, a regression analysis demonstrated that the number of away rotations was associated with matching to orthopedic surgery. 43 However, plastic surgery and orthopedic surgery are highly competitive disciplines and may not reflect all residency matches.…”
Section: Electivesmentioning
confidence: 99%
“…National Resident Matching Program (NRMP) data indicate that orthopaedic surgery programs fill >97% of postgraduate year 1 (PGY1) positions annually 1,2 . Additionally, the annual orthopaedic surgery residency match rate for U.S. seniors (i.e., fourth-year medical school students) historically varies between 75% and 80%, with up to one-quarter of applicants failing to match.…”
mentioning
confidence: 99%
“…17 Newer observational data from the 2 most competitive specialties are mixed 10 : an analysis of a plastic surgery match showed no effect of taking an away rotation, 18 while the study of an orthopedic surgery match showed a marked positive effect of taking 2 or more away rotations (odds ratio of matching ¼ 60.83, 95% CI 6.08-608.43). 19 In our survey, CDs recommended applying to a median of 10 programs for students in the highest academic quartile and 15 programs for students in the lowest quartile. These numbers are likely affected by the prestige of the medical school and may be different for students applying to more competitive specialties.…”
Section: Discussionmentioning
confidence: 97%